2017
DOI: 10.18869/mjiri.31.3
|View full text |Cite
|
Sign up to set email alerts
|

Common malignant cutaneous conditions among albinos in Kenya

Abstract: Background: Albinos in Africa are at constant risk of developing skin cancer due to the damage caused by ultra-violet exposure. This study identifies the common skin conditions among albinos in Kenya as a country located along the equator. Methods: In this descriptive study on albino patients who were admitted to Mbagathi District Hospital in Nairobi, Kenya the census method was used for sampling and a total of 151 albinos were registered. All necessary data including age, gender, type, site and the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 23 publications
7
19
1
1
Order By: Relevance
“…A study in Kenya involving 151 patients with albinism reported severe actinic lesions in 80% of patients, mostly Age, sun exposure, and sunburn were statistically significant (p < 0.05). between the ages of 21 and 30 years [29]. However, the African data and the current results differed substantially from the European reports.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A study in Kenya involving 151 patients with albinism reported severe actinic lesions in 80% of patients, mostly Age, sun exposure, and sunburn were statistically significant (p < 0.05). between the ages of 21 and 30 years [29]. However, the African data and the current results differed substantially from the European reports.…”
Section: Discussioncontrasting
confidence: 99%
“…3, 4). The tumors were preferentially located in the head and neck (42.6%), followed by the trunk (37%), and limbs (20.4%), which follows the trend of higher prevalence in the areas with most sun exposure [11,12,28,29,[31][32][33][35][36][37].…”
Section: Discussionmentioning
confidence: 76%
“…This disproportionately higher frequency of BCCs among the albino population is consistent with several reports showing BCCs to be more common than SCCs among Caucasians [27,28], fair-skinned normal pigmented Africans [6][7][8][9][10]29] and among albinos [17,30] than was earlier reported.…”
Section: Discussionsupporting
confidence: 89%
“…Although this differs from earlier studies which showed BCCs to be infrequent among African albinos [2,15], the finding of SCC/BCC ratio of 1:2.3 further confirms that both BCCs and SCCs occur commonly in albinos comparable to the ratios reported in other studies in Africa which found a ratio of 1: 1.5 [17,30], in lighter complexioned Africans [6][7][8][9] and in Caucasians [27,28] and closely approximates the ratio reported by Kiprono et al [18] in Tanzania (Table 2) which found an SCC/BCC ratio of 1.2: 1 and Ademola et al [19] at Ibadan, Nigeria, with a ratio of 1:1.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation